Physiological maturation of sweet sorghum seeds produced under water restriction - Costa Silva, Weslley; Gomes de Moura, Joana; Bosco de Oliveira, Alexandre; Susana Silva Batista, Maria; Lenin Marques de Brito, Leonardo; Chagas de Sousa, Kleyton (Revista Ciência Agronômica, 2023)
Sweet sorghum has been shown to be an alternative for ethanol production in several regions. Because it is sexually propagated, the use of quality seeds becomes an important factor for obtaining an adequate plant stand and, consequently, good productivity. Thus, the objective was to evaluate the production and physiological maturation of seeds of sweet sorghum cv. BRS 511, in response to the interval between irrigations during the reproductive period and harvesting period. Two experiments were carried out in a greenhouse, the experimental design adopted was in randomized blocks, with four replications in a 3 x 2 split-plot scheme, corresponding to three intervals between irrigations during the reproductive stage (0; 4 and 8 days) and two harvest times (102 and 110 days after sowing). The following parameters were evaluated from the harvested panicles: number of seeds, weight of one thousand seeds, water content, germination, first germination count, emergence in sand and emergence speed, electrical conductivity and seedling vigor. The production of seeds per panicle and the weight of a thousand seeds were signifi cantly infl uenced by the increase in the interval between irrigations in the 2nd experiment, with a reduction of 50.4 and 46.3%, respectively. Water replacement every eight days caused a reduction of up to 43.4% in the first germination count and 16.3% in germination. The production and quality of sweet sorghum seeds reduces as a function of the increase in the interval between irrigations and the harvesting time, presenting germination rates below the required for commercialization.